Efficiency of the resources of the general system of participation in the integral development of first childhood (2016)
The transfer of resources through the General System of Participations to territorial entities presents complex characteristics within the framework of the investment in early childhood programs, in CONPES 109 are established the public policy of early childhood and normative and conceptual referents, providing tools to attend needs of children from zero to five years around the national territory. The department of Boyacá, in accordance with national regulations, establishes through public ordinance 026 of 2010, the public policy "New Citizen of Boyacá", which aims to provide comprehensive care to all children in the department. So, the development of the present document intends to achieve a specific analysis of the investment situation and social spending through the General System of Participations for the care of the children in the Province of Oriente of the department.